TEORI MAQÂSHID SYARÎ’AH PERSPEKTIF AL-SYATIBI - Toriquddin, Moh (De Jure: Jurnal Hukum dan Syari'ah, 2014)
The discourse surrounding the theory maqÃ¢shid syarÃ®'ah is still worth doing it aims to understand who far Islamic lawÂ  is in lineÂ  with theÂ  progress of time. Theory maqÃ¢shidÂ  syarÃ®â€Ÿah Syathibi globally based on twoÂ  things: the problems ta'lil (legal determination basedÂ  illat), andÂ  al-mashÃ¢lihÂ  waÂ  al-mafÃ¢sidÂ  (benefitÂ  andÂ  damage). Furthermore, he explains howÂ  to determine maqÃ¢shid with six ways: goals syari'ah must beÂ  in accordanceÂ  with theÂ  Arabic language,Â  commandsÂ  andÂ  prohibitions syarÃ®â€Ÿah understood as ta'lÄ«l (have illat) and á¸ahiriyah (text what it is), maqÃ¢shid al-ashliyahÂ  (originÂ  destination)Â  waÂ  al-maqÃ¢shidÂ  al-tabi'iyyahÂ  (destinationÂ  followers), sukut al-syÃ¢riâ€ŸÂ  (silenceÂ  syÃ¢riâ€Ÿ), al-istiqra'Â  (theory of induction), looking for clues of the CompanionsÂ  of the Prophet.Â  For operatingÂ  of ijtihadÂ  al-Â  maqÃ¢shidy,Â  Syathibi requires four conditions as follows: texts and laws depending on the goal, collecting betweenÂ  kulliyÃ¢tÂ  al-'Ã¢mmahÂ  andÂ  specificÂ  arguments,Â  bringÂ  benefitÂ  and prevent damage to the absolute and considering the result of a law.